Aquatic hazard assessment of MON 0818, a commercial mixture of alkylamine ethoxylates commonly used in glyphosate‐containing herbicide formulations. Part 1: Species sensitivity distribution from laboratory acute exposures. (30th August 2016) - Rodriguez‐Gil, Jose L.; Prosser, Ryan; Poirier, David; Lissemore, Linda; Thompson, Dean; Hanson, Mark; Solomon, Keith R.
Abstract: The sensitivity of 15 aquatic species, including primary producers, benthic invertebrates, cladocerans, mollusks, and fish, to MON 0818, a commercial surfactant mixture of polyoxyethylene tallow amines, was evaluated in standard acute (48–96‐h) laboratory tests. In addition, the potential for chronic toxicity (8 d) was evaluated with Ceriodaphnia dubia . Exposure concentrations were confirmed. No significant effects on any endpoint were observed in the chronic test. A tier‐1 hazard assessment was conducted by comparing species sensitivity distributions based on the generated data, as well as literature data, with 4 exposure scenarios. This assessment showed moderate levels of hazard (43.1% of the species exposed at or above median effective concentration levels), for a chosen worst‐case scenario—unintentional direct over‐spray of a 15‐cm‐deep body of water with the maximum label application rate for the studied formulations (Roundup Original, Vision Forestry Herbicide; 12 L formulation ha −1, equivalent to 4.27 kg acid equivalent [a.e.] ha −1 ). The hazard decreased to impairment of 20.9% of species under the maximum application rate for more typical uses (6 L formulation ha −1, 2.14 kg a.e. ha −1 ), and down to 6.9% for a more frequently employed application rate (2.5 L formulation ha −1, 0.89 kg a.e. ha −1 ). Finally, the percentage (3.8%) was less than the hazardous concentration for 5% of the species based on concentrations of MON 0818 calculated from maximum measured concentrations of glyphosate in the environment. Environ Toxicol Chem 2017;36:501–511. © 2016 SETAC